Comparison of selected physical fitness components among male football players of different playing positions - Amandeep Sıngh; Sukhdev Sıngh; Vishaw Gaurav (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to examine the level of physical fitness among male football players in relation to their different playing positions i.e. goalkeepers, defenders, midfielders and attackers. A sample of forty (N = 40) male football players (mean ± SD: age 20.45 ± 1.70 years, height 1.84 ± 4.07 m, weight 81.62 ± 5.45 kg, BMI 23.99 ± 1.66m), which includes ten each goalkeepers, defenders, midfielders and attackers, who participated in inter-college competitions of Guru Nanak Dev University, Amritsar, India, was selected. All the participants were informed about aim and methodology of the study and they volunteered to participate in this study. The study was conducted on selected physical fitness variables i.e. power, speed and agility. One way Analysis of Variance (ANOVA) was applied to find out the significance of differences with regard to selected physical fitness variables among football players of different playing positions. Scheffe’s post-hoc test was applied to see the direction and significance of differences where ‘F’ value found statistically significant. The level of significance was set at 0.05. While comparing the means, it is revealed that midfielders and attackers had almost the same power, speed and agility. However, midfielders and attackers had shown better power and agility than their counterparts; goalkeepers and defenders. Further, significant differences were found between football players of different playing positions with regard to the variables power (p˂0.05) and agility (p˂0.05), but insignificant differences were found on the variable speed respectively (p˃0.05).